FAKTOR YANG MEMPENGARUHI KEJADIAN CARPAL TUNNEL SYNDROME PADA PERAJIN BATIK TULIS “SERULING ETAN” MAGETAN - Setyoaji, Dhaniswara; Jayanti, Siswi; Ekawati, Ekawati; Widjasena, Baju (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Improper workplace behavior is the main cause of Carpal Tunnel Syndrome. Carpal Tunnel Syndrome or secondary neurological diseases in the wrist, is a medical condition in which the central nervous depressed at the wrist resulting in patients experiencing numbness and weakness of the hand muscles. This research was conducted to determine the relationship between the factors that cause Carpal Tunnel Syndrome with incidence Carpal Tunnel Syndrome to the batik artisans at Seruling Etan. This research is an